2018
DOI: 10.3766/jaaa.16175
|View full text |Cite
|
Sign up to set email alerts
|

Higher Asymmetry Ratio and Refixation Saccades in Individuals with Motion Sickness

Abstract: Presence of higher asymmetry ratio in cVEMP and vHIT test results plus refixation saccades to stabilize the gaze in vHIT can suggest some amount of vestibular anomalies in individuals with motion sickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
4
13
1
2
Order By: Relevance
“…In our study, in accordance with the work of Neupane et al (Neupane et al, 2018), the asymmetry rates of the individuals with motion sickness were higher than those of the healthy individuals. However, the asymmetry rates of the anterior canals of the individuals with motion sickness were statistically higher than those of the healthy individuals, while no statistical difference was found in other canals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, in accordance with the work of Neupane et al (Neupane et al, 2018), the asymmetry rates of the individuals with motion sickness were higher than those of the healthy individuals. However, the asymmetry rates of the anterior canals of the individuals with motion sickness were statistically higher than those of the healthy individuals, while no statistical difference was found in other canals.…”
Section: Discussionsupporting
confidence: 93%
“…Neupane et al (Neupane et al, 2018) reported that all SSC VOR gains of the individuals with motion sickness were found to be statistically lower than those of the healthy individuals, which is in line with the results of the present study. Studies showing the decrease in VOR gains in individuals with peripheral vestibular pathology indicate the effect of motion sickness on the peripheral system (Weber et al, 2008, MacDougall et al, 2013.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…29,40,41 Blodow et al 31 suggested that compensatory refixation saccades occur as a result of reduced VOR gain in individuals with vestibulopathy. Also, the similar results obtained by Neupane et al 42 in individuals with motion sickness recommended compensatory refixation saccades as a good parameter in evaluating these individuals.…”
Section: Discussionsupporting
confidence: 75%
“…We found changes in VEMP asymmetry ratio, with a substantial increase in VEMP amplitude recorded on the left sternocleidomastoid muscle following just one minute of exposure to vection in VR. Similarly, VEMP asymmetry has been reported to positively correlate with susceptibility to motion sickness (Xie et al., ; Neupane, Gururaj, & Sinha, ; however, see Buyuklu, Tarhan, & Ozluoglu, , for contradictory findings). While our results showed changes in VEMP asymmetry following exposure to vection in VR, we did not find a correlation between VEMP amplitude and motion sickness susceptibility in our sample.…”
Section: Discussionmentioning
confidence: 92%